Determinants of Work Engagement for TNI-AD (Indonesian Armed Forces - Army) Personnel [Determinan Keterikatan Kerja Personel Tentara Nasional Indonesia - Angkatan Darat (TNI-AD)] - Aulia Aulia; Aftoni Sutanto; Abdul Choliq Hidayat (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
Work engagement is one of the important factors in the environment of an organization, because the positive impact of work engagement has a very significant influence on personal or organizational performance. This research was aimed at determining, in an empirical way, the connections between love of work, self-efficacy and the perception of organizational support, and military work engagement. The research used quantitative methods, and the methods of collection were in the form of scales, of the love of work, self-efficacy, the perception of organizational support, and work engagement. The population used for the research comprised all of the Tentara Nasional Indonesia - Angkatan Darat (TNI-AD - Indonesian Armed Forces - Army) personnel of Komando Distrik Militer (Kodim - Military District Command) X (not the real designation), between 35 and 60 years of age, of a range of ranks, with a minimum of 10 years of work experience. The sample data collection technique in the research employed probability, that being disproportioned stratified random sampling. The analysis technique for the research was that of multiple regression analysis. The results of the analysis indicated that love of work, self-efficacy and the perception of organizational support, jointly, have significant connections with a Regression Coefficient of R = .525, with the variables of love of work, self-efficacy, and perception of organizational support jointly making an effective contribution to the work engagement of the military personnel of Kodim X, that being 27.5%. Keterikatan kerja adalah salah satu faktor penting dalam lingkup organisasi, karena dampak positif dari keterikatan kerja berpengaruh sangat signifikan terhadap kinerja pribadi ataupun organisasi. Penelitian ini bertujuan untuk mengetahui secara empirik hubungan cinta pekerjaan, efikasi diri, dan persepsi dukungan organisasi terhadap keterikatan kerja tentara. Penelitian ini menggunakan metode kuantitatif dan alat pengumpulan data adalah skala, yang meliputi skala cinta pekerjaan, efikasi diri, persepsi dukungan organisasi, dan keterikatan kerja. Populasi yang digunakan pada penelitian ini yaitu seluruh personel Tentara Nasional Indonesia - Angkatan Darat (TNI-AD) di Komando Distrik Militer (Kodim) X yang berusia 35-60 tahun, dari berbagai jenis kepangkatan, dengan minimal masa kerja adalah 10 tahun, sementara teknik pengambilan sampel pada penelitian ini menggunakan probability yaitu disproportioned stratified random sampling. Teknik analisis data pada penelitian ini menggunakan analisis regresi berganda. Hasil analisis menunjukan bahwa secara bersama-sama cinta pekerjaan, efikasi diri, dan persepsi dukungan organisasi memiliki hubungan yang signifikan dengan koefisien regresi sebesar R = 0,525, dengan sumbangan efektif dari variabel cinta pekerjaan, efikasi diri, dan persepsi dukungan organisasi secara bersama-sama terhadap keterikatan kerja tentara di Kodim X adalah sebesar 27,5%. Received 3 August 2019; Accepted 30 September 2019; Published 25 October 2019.